A novel superior medication-based chronic disease score predicted all-cause mortality in independent geriatric cohorts - Quinzler, Renate; Brenner, Hermann; Freund, Tobias; Schöttker, Ben; Szecsenyi, Joachim; Haefeli, Walter E.; Freitag, Michael H. (Journal of clinical epidemiology, 2019)
Objectives - On the basis of current treatment guidelines, we developed and validated a medication-based chronic disease score (medCDS) and tested its association with all-cause mortality of older outpatients. - Study Design and Setting - Considering the most prevalent chronic diseases in the elderly German population, we compiled a list of evidence-based medicines used to treat these disorders. Based on this list, a score (medCDS) was developed to predict mortality using data of a large longitudinal cohort of older outpatients (training sample; MultiCare Cohort Study). By assessing receiver-operating characteristics (ROC) curves, the performance of medCDS was then confirmed in independent cohorts (ESTHER, KORA-Age) of community-dwelling older patients and compared with already existing medication-based scores and a score using selected anatomical-therapeutic-chemical (ATC) codes. - Results - The final medCDS score had an ROC area under the curve (AUC) of 0.73 (95% CI 0.70-0.76). In the validation cohorts, its ROC AUCs were 0.79 (0.76-0.82, KORA-Age) and 0.74 (0.71-0.78, ESTHER), which were superior to already existing medication-based scores (RxRisk, CDS) and scores based on pharmacological ATC code subgroups (ATC3) or age and sex alone (Age&Sex). - Conclusions - A new medCDS, which is based on actual treatment standards, predicts mortality of older outpatients significantly better than already existing scores.
Gesehen am 15.11.2018
Available online: 22 September 2018